2017
DOI: 10.7150/thno.18857
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Avian Influenza Virus by Fluorescent Diagnostic Assay using an Epitope-Derived Peptide

Abstract: Currently, the point of care testing (POCT) is not fully developed for subtype-specific avian influenza virus detection. In this study, an H5N1 hemaglutinin 1 (HA1) epitope (P0: KPNDAINF) and three modified peptides (P1: KPNTAINF, P2: KPNGAINF, P3: KPNDAINDAINF) were evaluated as POCT elements for rapid detection of avian influenza virus. Based on modeling predictions by Autodock Vina, binding affinity varied depending on alteration of one amino acid in these peptides. The binding energy of P2 indicated its po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Previously, we showed that peptide aptamers rather than antibodies could be used in diagnostic applications 21 . In the current study, peptide specificity was improved by modifying the binding sites in addition to enhancing the binding affinity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we showed that peptide aptamers rather than antibodies could be used in diagnostic applications 21 . In the current study, peptide specificity was improved by modifying the binding sites in addition to enhancing the binding affinity.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the interaction of candidate peptides with antigen and virus, Eu NPs were conjugated with peptides by forming a stable amide bond, and a FLISA was conducted as previously described 21 . The ZIKV envelope protein (amino acid 1-504) was cloned, and the recombinant antigen was produced in an Escherichia coli expression system; this antigen was used to make mAbs, and the reactivity of antibody to virus was confirmed via enzyme-linked immunoassay (ELISA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The operation time is around 15 min, which demonstrates the potential of rapid field-ready biosensor on site. This group went on to develop an epitope-derived peptide with europium nanoparticle to detect AIV H5N1 using the fluorescence-linked immunosorbent assay in the point-of-care testing (POCT) system [84]. This novel peptide can be used as the fluorescence signal reporter in the proposed detection system that can reduce the antibody size in the interface.…”
Section: Fluorescence (Fl)-based Detection Of Aiv Using Nanobio Hymentioning
confidence: 99%